Evaluation Deoxyribonucleic acid (DNA) fragmentation of local Indonesian cattle frozen sperm using Halomax method - TEGUH ARI PRABOWO; SIGIT BINTARA; LIES MIRA YUSIATI; PRADITA IUSTITA SITARESMI; DIAH TRI WIDAYATI (Society for Indonesian Biodiversity, 2023)
Abstract. Prabowo TA, Bintara S, Yusiati LM, Sitaresmi PI, Widayati. 2023. Evaluation Deoxyribonucleic acid (DNA) fragmentation of local Indonesian cattle frozen sperm using Halomax method. Biodiversitas 24: 2225-2230. Deoxyribonucleic acid (DNA) is a molecular chain containing genetic material that determines the quality of each individual produced. DNA damage in cattle can affect fertility and miscarriage of embryos. There is no simple research on DNA damage in local Indonesian cattle (Bos indicus Linnaeus 1758); therefore, miscarriage and infertility cases in Indonesia are still high, one of which can be attributed to sperm DNA damage. This study aimed to evaluate DNA damage in the frozen semen of local Indonesian cattle and suggested SDF (Sperm DNA Fragmentation) inclusion screening as the main requirement for frozen semen. The materials used in this study were 54 straws of frozen semen from nine males from three different types of local cattle, including Bali, Madura, and Aceh. Each type consisted of three bulls, each with six replicates. Sperm-Bos-Halomax was used to examine sperm DNA damage. Data were analyzed using one-way analysis of variance (ANOVA). Aceh cattle had the highest post average compared to Bali and Madura at 63.33±2.43%. Abnormality of Balinese cattle had the lowest average compared to Aceh and Madura at 8.83±1.04%. Evaluation of sperm DNA damage in local cattle using the Sperm-Bos-Halomax® method showed that the highest average DNA damage was 1.72±0.62% in Aceh, and the lowest was 1.67±0.66% in Madura cattle. The sperm DNA damage in Bali cattle was 1.67±0.70%. The sperm DNA quality in the frozen semen of the local cattle in this study was good, but it is still necessary to determine SDF as the main standard in frozen semen.